2017
DOI: 10.1111/acer.13401
|View full text |Cite
|
Sign up to set email alerts
|

Eveningness and Later Sleep Timing Are Associated with Greater Risk for Alcohol and Marijuana Use in Adolescence: Initial Findings from the National Consortium on Alcohol and Neurodevelopment in Adolescence Study

Abstract: BACKGROUND Abundant cross-sectional evidence links eveningness (a preference for later sleep-wake timing) and increased alcohol and drug use among adolescents and young adults. However, longitudinal studies are needed to examine whether eveningness is a risk factor for subsequent alcohol and drug use, particularly during adolescence, which is marked by parallel peaks in eveningness and risk for the onset of alcohol use disorders. The present study examined whether eveningness and other sleep characteristics we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
79
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 66 publications
8
79
4
Order By: Relevance
“…This effect appears strong in early development, such that early childhood sleep deficits predict cannabis use in later adolescence 22,42-44 and sleep factors during adolescence predict adult cannabis use 21, 45 . Lastly, endorsements of an adolescent eveningness chronotype is associated with follow-up reports of increased cannabis use controlling for baseline adolescent substance use 40 . With evidence of both crosssectional associations and a bidirectional relationship between cannabis and sleep deficits/eveningness chronotype, there could be an underlying common liability such as shared or common genetics responsible for this association.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This effect appears strong in early development, such that early childhood sleep deficits predict cannabis use in later adolescence 22,42-44 and sleep factors during adolescence predict adult cannabis use 21, 45 . Lastly, endorsements of an adolescent eveningness chronotype is associated with follow-up reports of increased cannabis use controlling for baseline adolescent substance use 40 . With evidence of both crosssectional associations and a bidirectional relationship between cannabis and sleep deficits/eveningness chronotype, there could be an underlying common liability such as shared or common genetics responsible for this association.…”
Section: Introductionmentioning
confidence: 94%
“…Evidence exists for the reverse relationship as well, with premorbid insomnia 21 and generalized sleep problems [39][40][41] predicting later cannabis use. This effect appears strong in early development, such that early childhood sleep deficits predict cannabis use in later adolescence 22,42-44 and sleep factors during adolescence predict adult cannabis use 21, 45 .…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, some studies link self‐reports of actual sleep timing (which may or may not correspond to preferred timing) to alcohol use (Pasch et al., ; Pieters et al., ). Longitudinal evidence suggests that both evening chronotype and later actual sleep timing predict more extreme binge alcohol use a year later (Hasler et al., ). Notably, eveningness is often accompanied by more variable sleep timing (Soehner et al., ; Wittmann et al., ), which is also associated with alcohol involvement and thus is a hypothesized factor linking eveningness and alcohol problems (Wittmann et al., ).…”
Section: Sleep Timing Eveningness and Alcohol Responsementioning
confidence: 99%
“…In 236 healthy adolescents (age 13–16 years: Anderson et al, 2009 ), increased sleepiness was significantly associated with more problems on dimensions including Working Memory, Task Planning, Orderliness, and Task Completion (i.e., BRIEF Metacognition) and not associated with Inhibitory Control, Flexibility, Emotional Control and Monitoring (i.e., BRIEF Behavioral Regulation). Sleep problems and circadian misalignment have been found to predict adolescent alcohol and other substance use (Hasler and Clark, 2013 ; Hasler et al, 2014 , 2016 , 2017 ). A study with a larger sample is needed to determine whether the relationships observed between executive dysfunction and poor sleep (Anderson et al, 2009 ) can be confirmed.…”
Section: Introductionmentioning
confidence: 99%